PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, LEVERAGE, DAN PROFITABILITAS TERHADAP LUAS PENGUNGKAPAN - Listyorini Wahyu Widati; Rosaliana Wigati (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2011)
This research is a study that tested the effect of firm size, liquidity, leverage and profitability with agency theory perspective. Basic need for financial statement disclosure practices by management to shareholders described inagency theory. Firm size, liquidity, leverage and profitability will determine the extent of disclosure. In this research, the sampling technique used was purposive sampling and obtain a sample of 62 companies. Thecompany's data and then tested with normality, multicollinearity, heteroscedasticity and autocorrelation. The results showed normal data and avoid the classical assumption violations. Subsequent analysis is the use ofmultiple linear regression to explain the influence between these variables. The result is a positive firm size is not significant, liquidity and leverage significant negative effect. While significant positive effect on theprofitability of Mandatory Disclosure. Thus the higher profitability will increase broad disclosure.Key words: firm size, liquidity, leverage profitability and disclosure